Public preventive awareness and preventive behaviors during a major influenza epidemic in Fukui, Japan - Shintoku Takahashi; Kazuhiro Sato; Yukinori Kusaka; Akihito Hagihara (Elsevier, 2017)
Background: As an influenza epidemic poses a serious public health threat, it is important for the public to adopt behaviors that effectively prevent influenza infection. Methods: In the winter of 2009, by using a structured questionnaire, we conducted an Internet survey with respect to residents (n = 2788) in Fukui prefecture, Japan. The main aim is to obtain information about effective prevention, factors related to preventive awareness and behaviors during the influenza epidemic. A factor analysis and linear regression models were used in the analysis. Results: Three types of preventive awareness were identified by factor analysis: "avoidance of influenza infection," "awareness of the benefits of mask use," and "awareness of the need for a rapid diagnosis." Gender, age, residence, being medical person and being vaccinated were related to these preventive awareness and behaviors. Avoidance of influenza Infection was related to all preventive behavior, awareness of the benefits of mask use was related to hand disinfectant use, and awareness of the need for a rapid diagnosis was related to avoidance of face touch, gargling and attention to health care, respectively. Conclusion: Three types of preventive awareness during the influenza epidemic were emerged, and were related to preventive behaviors against influenza infection. Keywords: Infection, Influenza, Epidemic, Preventive awareness, Preventive behavior